The Role of Writing in Distributed Collaboration - Fayard, Anne-Laure; Metiu, Anca (Organization Science, 2014)
Distributed collaborations face significant dialogical challenges: sharing knowledge, questioning ideas, and developing new solutions. These challenges are often associated with collaborations' reliance on written communication such as emails and documents, which are not seen as conducive to the rich dialogues necessary for effective collaboration. However, numerous successful distributed collaborations exist despite their sometimes exclusive reliance on written communication. Based on a qualitative study of distributed collaboration in two contexts—an organization effectively coordinating work across two continents and a pair of scientists working together to develop a new theory—we examine how writing supports dialogue, and thus collaboration, among distant partners. Our analysis of the correspondences exchanged in these two historical distributed collaborations identifies four mechanisms of writing—objectifying, contextualizing, specifying, and reflecting—and shows how they support dialogue and so address the dialogical challenges involved in distributed collaboration. These findings are particularly relevant in our era of technology-mediated communication where even collaborations in colocated settings rely extensively on written communication. Our findings advance our understanding of fundamental aspects of distributed collaboration and propose to rethink the value of written communication in enacting dialogue and supporting collaboration at a distance.